Pressure‐Induced Superconductivity in HgTe Single‐Crystal Film. Issue 18 (25th April 2022) - Li, Qiang; Zhang, Jian; Zheng, Qunfei; Guo, Wenyu; Cao, Jiangming; Jin, Meiling; Zhang, Xingyu; Li, Nana; Wu, Yanhui; Ye, Xiang; Chen, Pingping; Zhu, Jinlong; et al.
Abstract: HgTe film is widely used for quantum Hall well studies and devices, as it has unique properties, like band gap inversion, carrier‐type switch, and topological evolution depending on the film thickness modulation near the so‐called critical thickness (63.5 Å), while its counterpart bulk materials do not hold these nontrivial properties at ambient pressure. Here, much richer transport properties emerging in bulk HgTe crystal through pressure‐tuning are reported. Not only the above‐mentioned abnormal properties can be realized in a 400 nm thick bulk HgTe single crystal, but superconductivity is also discovered in a series of high‐pressure phases. Combining crystal structure, electrical transport, and Hall coefficient measurements, a p‐n carrier type switching is observed in the first high‐pressure cinnabar phase. Superconductivity emerges after the semiconductor‐to‐metal transition at 3.9 GPa and persists up to 54 GPa, crossing four high‐pressure phases with an increased upper critical field. Density functional theory calculations confirm that a surface‐dominated topologic band structure contributes these exotic properties under high pressure. This discovery presents broad and efficient tuning effects by pressure on the lattice structure and electronic modulations compared to the thickness‐dependent critical properties in 2D and 3D topologic insulators and semimetals. Abstract : HgTe is widely used for quantum Hall well studies in thin film form. Under pressure, it undergoes a semiconductor‐to‐metal transition (≈3.5 GPa), followed by superconducting behavior up to 54 GPa, across four high pressure phases. Density functional theory calculation confirms that a surface‐dominated topologic band structure contributes the exotic properties under high pressure.